Salem's Lot - king, Stephen (London Hodder & Stoughton (Hachette India), 2021)
'Salem's Lot is a vampire story which is thrilling and full of horror. The book is amongst the bestsellers series by the author. The story revolves round a small town in England that is infested by vampires, with two people trying to fight them and free the town. It is adventurous and spine-chilling till the end.The protagonist of the story is a writer named Ben Mears. He returns to his hometown after twenty five years, befriends a school teacher named Matt Burke and falls in love with Susan Norton. He starts writing a book about the abandoned Marsten House, of which he has bad memories as a child. The house gets bought by a businessman named Kurt Barlow, who is more of a traveller and his business partner Richard Straker also arrives at the house. Soon a small boy disappears, and his brother Danny dies and becomes a vampire. He infects a lot of people in the town. Barlow captures Susan and makes her a vampire. To stop this rampage on the town Ben, Matt, his doctor Jimmy Cody, young Mark Petrie, and the local priest Father Callahan get - together to fight the vampires. The group is attacked by the vampires, particularly by Barlow. Jimmy Cody is killed. Ben and Mark flee from the town, after successfully killing Barlow.'Salem's Lot was published by Hodder Paperbacks in 2011. It is available in paperback. Key Features: The book was nominated for a World Fantasy Award for Best Novel in 1976.
Keywords: English Fiction